Association of Household Environment and Prevalence of Anemia Among Children Under-5 in India - Baranwal, Annu; Baranwal, Anshu; Roy, Nobhojit (Frontiers in Public Health, 2014)
Objective: The study explores the association between the household environment and the prevalence of anaemia among children under the age of five years in India. Data and methodology: The study is based on 52,868 children under the age of five years, included in India’s National Family Health Survey-3. The outcome variable was the prevalence of anaemia. To understand the role of environment in determining child anaemia, step wise logistic regression models consisting of environmental, child, socio-economic and media exposure variables were applied. Results: The occurrence of childhood anaemia was higher in the North Eastern and Eastern regions compared to all other regions of India. Unclean fuel use, poor toilet facilities, staying in non-concrete house, exposure to smoking were important variables determining the prevalence of anaemia. Smoking when it was controlled with only socio economic factors showed lesser impact on anaemia but when it got adjusted with socio-economic, child and media variables together it showed an important impact as it increased the risk of anaemia. Conclusion: Children under five years of age generally stay inside their house and are more exposed to the household environment. Thus, among these children there are multiple risk factors causing anaemia along with the nutritional deficiencies. Better resources are needed to educate the public and to increase awareness for improved hygiene, sanitation and housing facilities, health and nutrition etc. Along with a wider programme to manage nutritional deficiency anaemia in children less than five years, there should be a holistic approach towards anaemia control inculcating household environmental conditions and socio economic determinants.